Sharp decay estimates for the Vlasov–Poisson system with an external magnetic field. (February 2022) - Wu, Man
Abstract: In this paper, we establish sharp decay estimates for the Vlasov–Poisson system with an external magnetic field on R x 3 × R v 3 . Our arguments are based on the modified vector field method developed in Smulevici (2016) for the classical Vlasov–Poisson system in the 3–D case, and hence we extend some results in Smulevici (2016) to the Vlasov–Poisson system with an external magnetic field.